Microbacterium caowuchunii sp. nov. and Microbacterium lushaniae sp. nov., isolated from plateau pika (Ochotona curzoniae) on the Qinghai–Tibet Plateau of PR China. Issue 2 (27th February 2021) - Tian, Zhi; Yang, Jing; Lai, Xin-He; Pu, Ji; Jin, Dong; Luo, Xuelian; Huang, Ying; Li, Junqin; Zhang, Gui; Wang, Suping; Xu, Jianguo
Abstract : Four novel bacterial strains (ST-M6 T, L-033, L-031 T and Z-333) were isolated from the intestinal contents of plateau pikas ( Ochotona curzoniae ) collected on the Qinghai – Tibet Plateau, PR China. Cells were aerobic, non-motile, Gram-stain-positive, catalase-positive, oxidase-negative, capsuled and short-rod-shaped. Phylogenetic analyses based on the 16S rRNA gene sequences and 387 core genes indicated that the four isolates belong in the genus Microbacterium and clearly separate from recognized species. The two type strains (ST-M6 T and L-031 T ) shared low 16S rRNA similarity, average nucleotide identity values and digital DNA–DNA hybridization relatedness with their phylogenetic neighbours ( Microbacterium ginsengisoli DSM 18659 T, Microbacterium hatanonis DSM 19179 T, Microbacterium rhizomatis JCM 30598 T, Microbacterium radiodurans CCTCC M208212 T, Microbacterium oleivorans DSM 16091 T and Microbacterium arborescens DSM 20754 T ). The genomic DNA G+C contents of strains ST-M6 T and L-031 T were 70.4 and 70.7 mol%, respectively. The major cellular fatty acids of strain ST-M6 T were anteiso-C15 : 0, anteiso-C17 : 0 and iso-C16 : 0, in contrast to anteiso-C17 : 0, anteiso-C15 : 0 and anteiso-C17 : 1  ω 9 c of strain L-031 T . Both type strains (ST-M6 T and L-031 T ) were glycolate test positive and shared the following common features: MK-11 and MK-12 as major menaquinones; rhamnose, ribose, mannose and galactose as major cell-wall sugars; diphosphatidylglycerol, phosphatidylglycerol and two glycolipids as polar lipids; and ornithine, alanine, glycine and glutamic acid as cell-wall amino acids. Comparing the phenotypic, phylogenetic and chemotaxonomic features of the four strains and their related taxa, strains ST-M6 T and L-031 T represent two novel species of the genus Microbacterium, for which the names Microbacterium caowuchunii sp. nov. (type strain ST-M6 T =CGMCC 1.16364 T =DSM 104058 T ) and Microbacterium lushaniae sp. nov. (type strain L-031 T =CGMCC 1.16363 T =DSM 106170 T ) are proposed.